2013
DOI: 10.1080/07315724.2013.767672
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptance and Preference Study (CAPS) on Brown and Undermilled Indian Rice Varieties in Chennai, India

Abstract: Objectives To study consumer acceptance of unmilled brown and under milled rice among urban south Indians. Methods Overweight and normal weight adults living in slum and non-slum residences in Chennai participated (n=82). Bapatla (BPT) and Uma (red pigmented) rice varieties were chosen. These rice varieties were dehusked (unmilled, 0% polish) and further milled to 2.3% and 4.4% polishing (under milled). Thus nine rice samples in both raw and parboiled forms were provided for consumer tasting over a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 20 publications
6
31
1
Order By: Relevance
“…In our previous short-term trial using continuous glucose monitoring, replacing white rice with brown rice significantly reduced the 24-h glycaemic response and fasting insulinaemic response among overweight South Indians (7) . These findings, combined with our previous qualitative studies in a similar South Indian population, which identified strategies to increase acceptability of brown rice and demonstrated willingness to participate in a brown rice intervention, provided the rationale for the present trial (8)(9)(10)(11) . Here we aimed to investigate the effect of substituting brown rice for white rice on metabolic markers of T2D risk among adults in urban South India.…”
mentioning
confidence: 79%
“…In our previous short-term trial using continuous glucose monitoring, replacing white rice with brown rice significantly reduced the 24-h glycaemic response and fasting insulinaemic response among overweight South Indians (7) . These findings, combined with our previous qualitative studies in a similar South Indian population, which identified strategies to increase acceptability of brown rice and demonstrated willingness to participate in a brown rice intervention, provided the rationale for the present trial (8)(9)(10)(11) . Here we aimed to investigate the effect of substituting brown rice for white rice on metabolic markers of T2D risk among adults in urban South India.…”
mentioning
confidence: 79%
“…Thus, the work conducted at MDRF has focused on investigating the feasibility and cultural acceptability of substituting brown rice and under-milled rice, for polished white rice, using focus groups and taste tests among healthy-weight and overweight adults. Findings indicated that although most participants preferred white rice, they were willing to switch to brown or undermilled rice provided that it was affordable and they received education regarding its health benefits [ 114 ]. Additional suggestions to promote brown rice included advertising special recipes, celebrity endorsement, dispensing free samples and government-initiated education campaigns [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hunger is a physiological response when the stomach is empty. This is influenced by the work of the body's systems, namely the physiological peripherals and metabolic processes that will be linked to the work of the brain (Sudha et al, 2013). Assessment of initial satiety level is needed to determine the satiety index or the value of adding satiety after consuming the sample later.…”
Section: Initial Satiety Levelmentioning
confidence: 99%